Quasi-static and shock-wave loading of ultrafine-grained aluminum: effect of microstructural characteristics - Ivanov, K. V. (Journal of materials science)
The interrelation between microstructural characteristics and mechanical properties under quasi-static and shock-wave (dynamic) loading was investigated in ultrafine-grained aluminum processed by accumulative roll bonding (ARB) for 4, 7, 10 and 14 cycles. The microstructural parameters such as the size of the elements of grain-subgrain structure, grain size and fraction of high-angle grain boundaries were obtained using transmission electron microscopy (TEM) and electron back scatter diffraction (EBSD). Indentation and tensile tests at the strain rate of 1 × 10−4 s−1 were applied as the quasi-static loading, the impact by aluminum flyer-plates with the impact velocity of 620 ± 30 m s−1 was the shock-wave loading. The strain rate in the rarefaction wave before spall fracture was 2 × 105-7 × 105 s−1 in the latter case. It is shown that the dislocation substructures and low-angle subboundaries significantly affect the strength properties under quasi-static conditions, while the grain size (the areas bounded by only high-angle boundaries) and fraction of high-angle grain boundaries mainly define the dynamic strength properties. The different influence of the microstructural characteristics on the quasi-static and dynamic mechanical properties is related to the easier dislocation cross-slip under high strain rates.